Influence of participatory decision making on job satisfaction: evidence from an Islamic tertiary institution with moderating role of staff experience - Abdulwahab Al-Daba, Abdulmajid Mohamed; Mohd Ali, Hairuddin; Alshuhumi, Said R. A.; Paramboor, Jafar (IIUM Press, 2021)
The relationship between participatory decision-making (PDM) and job satisfaction (JS) has attracted the attention of researchers not only in the field of business industries but also education sector. However, the issue has not been given noteworthy priority in educational administration research let alone in Islamic tertiary institution context. Thus, the purpose of this study is threefold: 1) to validate the psychometric properties of administrative staff’s PDM and JS constructs, 2) to examine the degree of influence of administrative staff’s PDM on their JS, and 3) test the moderating role of staff’s working experience on the influence of PDM on JS. Using a quantitative survey approach, data were collected from 255 administrative staff working in different faculties, divisions, and centers of International Islamic University Malaysia (IIUM). The study employed co-variance-based SEM by using AMOS version 24 in order to achieve the objectives. First, Confirmatory Factor Analysis (CFA) was employed to test the psychometric properties (such as convergent validity, divergent validity, and reliability) for both PDM and JS. Second, a Full-Fledged SEM was conducted to test the influence of PDM on JS. Finally, to examine the moderating effect of the staff working experience in the relationship between PDM and JST, a multi-group analysis (MGA) was applied. The results confirmed that the multidimensional hypothesized model of PDM and JS were empirically valid and reliable. The results also revealed a statistically significant impact for PDM on JS. Besides, the working experience was found to have a moderating role in the effect of PDM on JS. The study suggests that administrative staff involvement in decision making process is highly required as it increases their job satisfaction.